Pemberdayaan Pemuda Desa Dalam Strategi Promosi Digital Pada Wisata Gunung Mange Desa Sidorejo Kecamatan Sukorejo Kabupaten Ponorogo - Pradana, Angga Sandya; Anggoro, Ayub Dwi; Gestansi, Rohfin Andria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Community empowerment is a growth process. The purpose of this study was to find out the promotion strategy carried out by the youth of Sidorejo Village in managing Mount Mangge tourism. This study uses qualitative methods by extracting data based on phenomena and field facts which are carried out in depth. The location of this research is in Sidorejo Village, Sukorejo District, Ponorogo Regency. Data collection techniques in this study are by observation, interviews and documentation. Based on the results of the study, it stated that empowering village youth was carried out to form human resources who were experts in the field of digital promotion. The strategy used by village youths is by communicating using social networks such as Facebook, Instagram, and Twitter as well as websites displaying information about Mount Mangge, including pictures of the peak and its facilities to attract tourists.